Quantification and Characterization of Nanoparticulate Zinc in an Urban Watershed - Bevers, Shaun; Montaño, Manuel David; Rybicki, Laya; Hofmann, Thilo; von der Kammer, Frank; Ranville, James F. (Frontiers in Environmental Science, 2020)
The recent expansion in the use of nanomaterials in consumer and industrial applications has led to a growing concern over their behavior, fate, and impacts in environmental systems. However, engineered nanoparticles comprise only a small fraction of the total nanoparticle mass in aquatic systems. Human activities, particularly in urban watersheds, are increasing the population of incidental nanoparticles and are likely altering the cycling of more abundant natural nanoparticles. Accurate detection, quantification, characterization, and tracking of these different populations is important for assessing both the ecological risks of anthropogenic particles, and their impact on environmental health. The urban portion of the South Platte watershed in Denver, Colorado (USA) was sampled for zinc to identify and quantify different nanomaterial sources. Single particle ICP-QMS was employed, to provide single elemental (Zn) signals arising from particle detection events. Coupling spICP-QMS to sample pre-fractionation (sedimentation, filtration) provided some insights into Zn association with nanoparticulate, colloidal, and suspended sediment phases. Single particle ICP-TOFMS (spICP-TOFMS) provided quantification across a large atomic mass range, yielding an even more detailed characterization (elemental ratios) on a particle-by-particle basis, providing some delineation of multiple sources of particles. Across the watershed, on average, 21% of zinc mass was present as zinc-only particles with a rather uniform mean size of 40.2 nm. Zinc that was detected with one or more other elements, primarily Al, Fe, and Si, is likely to be present as heteroagglomerates or within mineral colloids. Although spICP-TOFMS provides a substantial amount of information, it is still in its early stages as an analytical technique and currently lacks the requisite sensitivity to study the smallest of nanoparticles. As this technique continues to develop, it is anticipated that this methodology can be broadly applied to study sources, behavior and effects of a disparate variety of nanoparticles from both geogenic and anthropogenic origins.